Triggers of Preoperative Anxiety in Patients Undergoing Mohs Micrographic Surgery. Issue 8 (August 2021) - Kruchevsky, Dani; Hirth, Jacob; Capucha, Tal; Ullmann, Yehuda; Ramon, Yitzchak
Abstract : Supplemental Digital Content is Available in the Text.